(untitled) (Cadernos de Sociomuseologia, 2018)
To regard museology, in a special way, the so-called social museology or sociomuseology, conversing with ideas and notions that might be considered obvious, but which, perhaps, if examined by another angle, have something new to offer, is part of this essay’s objectives. Besides, it is relevant to ask: to whom is the obvious, obvious? Frequently, that which seems obvious to certain groups of specialists may not be obvious to a great majority of people. It’s in this sense that, wandering through obviousness, we may affirm that Social Museology or Sociomuseology did not arise out of nowhere and neither is it the result of illuminated intellectuals who brought out of themselves, of their essences, the museal or museistic light that was to illuminate the world; on the contrary, it emerged from wide-ranging discussions and clashes, of built-up of tensions, criticism, confrontations, experiences, reflections and practices that impacted museology and museums which had advanced from the 19th century into the 20th without submitting their paradigms to a critical analysis.In other words: social museology, or sociomuseology, is not the result of a theoretical construction that wants, at any cost, from the top down, to frame museums and different forms of thinking and practicing museology to its technical, scientific, artistic and philosophical dictates; on the contrary, it is a construction resulting from a specific historical context, that doesn’t have, and doesn’t want to have, a normative character; that presents singular answers to also singular problems and that, above all, explicitly assumes political and poetical commitments. Keywords: Museology; social museology; sociomuseology; education; memory; social role of museums.